2013
DOI: 10.1073/pnas.1307170110
|View full text |Cite
|
Sign up to set email alerts
|

Higd-1a interacts with Opa1 and is required for the morphological and functional integrity of mitochondria

Abstract: The activity and morphology of mitochondria are maintained by dynamic fusion and fission processes regulated by a group of proteins residing in, or attached to, their inner and outer membranes. Hypoxia-induced gene domain protein-1a (Higd-1a)/HIMP1-a/HIG1, a mitochondrial inner membrane protein, plays a role in cell survival under hypoxic conditions. In the present study, we showed that Higd-1a depletion resulted in mitochondrial fission, depletion of mtDNA, disorganization of cristae, and growth retardation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 36 publications
2
46
1
Order By: Relevance
“…Higd1a augments cell survival under hypoxic stress in pancreatic cells (26), and it exerts its protective effect by induction of mitochondrial fission (27). The precise relationship between these reports and our data is not clear.…”
Section: Discussioncontrasting
confidence: 52%
“…Higd1a augments cell survival under hypoxic stress in pancreatic cells (26), and it exerts its protective effect by induction of mitochondrial fission (27). The precise relationship between these reports and our data is not clear.…”
Section: Discussioncontrasting
confidence: 52%
“…Mitofilins are inner membrane proteins, which are also involved in the cristae junctions' maintenance [55]; Together with OPA1, they form a complex network required to conserve the mitochondrial cristae structure. Recently, a new protein has been found to be involved in regulating mitochondrial fusion [56]. The hypoxia-induced gene domain protein-1a (Higd-1a) is a mitochondrial inner membrane protein.…”
Section: Mitochondrial Fusionmentioning
confidence: 99%
“…However, the over-expression of OPA1 did not appear to protect against ischemia-induced apoptosis and actually worsened it (50). In contrast to these findings, An et al (38) observed that OPA1 overexpression was protective against a hypoxic insult in HEK293T cells. Furthermore, Chen et al (51) noted that murine cardiomyocytes isolated from adult mice were more susceptible to cell death induced by simulated I/R injury suggesting a cardio-protective role for OPA1.…”
Section: Opa1 and Ischemia/reperfusion Injurymentioning
confidence: 89%
“…The exact interaction between ROMO1 and OPA1 is unclear, but it has been proposed that by attenuating oxidative stress, ROMO1 acts to reduce the activation of OMA1 thereby preventing the proteolytic cleavage of OPA1 (36). Finally, Hypoxia-induced gene domain protein 1 (Higd-1a), an IMM protein which has been reported to suppress mitochondrial cytochrome c release and inhibit apoptotic cell death under conditions of hypoxia, has been recently linked to OPA1 function (37,38). It has been shown to bind to and prevent the cleavage of l-OPA1 into s-OPA1, thereby attenuating cytochrome C release and inhibiting carbonyl cyanide-4-phenylhydrazone (FCCP)-induced mitochondrial fission and cell death (38).…”
Section: Other Regulators Of Opa1 Functionmentioning
confidence: 99%
See 1 more Smart Citation